2020
DOI: 10.18800/psico.202001.011
|View full text |Cite
|
Sign up to set email alerts
|

Perfiles de riesgo de deserción en estudiantes de las sedes de una universidad colombiana

Abstract: El estudio tuvo como objetivo determinar el perfil de riesgo de deserción según condiciones socioeconómicas, institucionales, académicas e individuales en estudiantes de las sedes de una universidad colombiana. Se realizó un estudio de corte transversal con una muestra aleatoria de 1897 estudiantes. Se utilizaron el Cuestionario de Vivencias Académicas QVA-r y el APGAR familiar. Se realizó un análisis de correspondencias múltiples utilizando la clasificación mixta para obtener las tipologías a partir de las co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 8 publications
1
12
0
14
Order By: Relevance
“…However, the participants report having good relationships with friends in the university environment and seeking support when required. With regard to family aspects, 16.2% affirmed having children, 33.3% were related to living in nuclear families, and 12.8% perceived having severe family dysfunction (25), a relationship can be evidenced with results regarding the academic average (3.49), marital status (single), socioeconomic stratum (stratum 1 and 2), in relation to family functionality it was found that 91% of students have good family functionality, not However, 14.3% of the participants in the present study stated that they intended to withdraw from the university.…”
Section: Discussionmentioning
confidence: 99%
“…However, the participants report having good relationships with friends in the university environment and seeking support when required. With regard to family aspects, 16.2% affirmed having children, 33.3% were related to living in nuclear families, and 12.8% perceived having severe family dysfunction (25), a relationship can be evidenced with results regarding the academic average (3.49), marital status (single), socioeconomic stratum (stratum 1 and 2), in relation to family functionality it was found that 91% of students have good family functionality, not However, 14.3% of the participants in the present study stated that they intended to withdraw from the university.…”
Section: Discussionmentioning
confidence: 99%
“…Students from these areas usually have adverse economic conditions that can potentially affect their academic performance and capacity to attend traditional classes. For this reason, the possibility of attending asynchronous pre-recorded classes, such as those implemented in this study, will positively impact the academic performance of this group of students and contribute to reducing desertion, a situation that has markedly increased in Colombia for years [21].…”
Section: Discussionmentioning
confidence: 99%
“…El abandono puede ser voluntario o forzoso, puede estar influenciada por intereses propios del estudiante, mientras que si la decisión es forzosa puede estar asociada a diferentes variables sociales, académicos, instituciones y económicos. Esta decisión puede además estar ocasionada por la baja proyección de la carrera elegida, bajo análisis acerca del curriculum y poca interacción con pares y profesores (Chong Ramírez-Rueda, Urrego-Velásquez, Páez-Zapata, Velásquez, & Hernández Ramírez, 2008;Tinto, 1989;Tomás & Gutiérrez, 2019;Zavala-Guirado, 2018).…”
Section: Desarrollounclassified